REGULATING MORALITY AND MEDIA ETHICS: A CRITICAL ANALYSIS OF PEMRA’S ROLE IN PAKISTAN’S BROADCAST LANDSCAPE (Contemporary Journal of Social Science Review, 2025)
The Pakistan Electronic Media Regulatory Authority (PEMRA) has a crucial role to play in ensuring that people embrace ethical and moral conduct in the Pakistani media. The authority, which has been established in accordance with the PEMRA Ordinance, 2002, controls television, radio, and cable channels in such a way that the content of the broadcast systems or media conforms to the national values, religious sensitivities, and social norms. The PEMRA code of ethics is more focused on being accurate, decently minded, respectful to cultural and spiritual feelings, and avoiding hate speech, obscenity, or subjects that could offend societal morals.Enhancing institutional independence and embracing technology-driven, transparent monitoring can help improve the ability of PEMRA to enforce ethics and morality in Pakistani media and promote democratic communication and social harmony.